2005
DOI: 10.1016/j.molcel.2005.04.015
|View full text |Cite
|
Sign up to set email alerts
|

ATM-Dependent Phosphorylation of ATF2 Is Required for the DNA Damage Response

Abstract: Activating transcription factor 2 (ATF2) is regulated by JNK/p38 in response to stress. Here, we demonstrate that the protein kinase ATM phosphorylates ATF2 on serines 490 and 498 following ionizing radiation (IR). Phosphoantibodies to ATF2(490/8) reveal dose- and time-dependent phosphorylation of ATF2 by ATM that results in its rapid colocalization with gamma-H2AX and MRN components into IR-induced foci (IRIF). Inhibition of ATF2 expression decreased recruitment of Mre11 to IRIF, abrogated S phase checkpoint,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 43 publications
5
140
1
Order By: Relevance
“…In contrast, however, previous studies suggested a tumor-promoting role of ATF2 in melanoma (12)(13)(14)(15)(16)(17). Similarly, Notch1 functions as a tumor suppressor in mouse skin, as opposed to its function as an oncogene in other organs (44).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, however, previous studies suggested a tumor-promoting role of ATF2 in melanoma (12)(13)(14)(15)(16)(17). Similarly, Notch1 functions as a tumor suppressor in mouse skin, as opposed to its function as an oncogene in other organs (44).…”
Section: Discussionmentioning
confidence: 91%
“…ATF2 target genes include AP1-responsive genes, such as cyclin A, IFN-␤, and TNF-␣ (9-11). Intriguingly, ATF2 has also been implicated in the DNA damage response, through its phosphorylation by phosphoinositide-3-kinase-related protein kinase, including ATM (12). This phosphorylation is required for intra-S phase checkpoint control and for its colocalization with components of the Mre11-Rad50-Nbs1 (MRN) complex within DNA damage repair foci.…”
mentioning
confidence: 99%
“…It is becoming evident that while the cellular response to DNA damage relies on a core of DDR-dedicated proteins, many of its arms are based on temporary recruitment of proteins or functional modules that normally operate in other processes. Indeed, it has been shown that the DDR temporarily calls into action proteins that normally act in other contexts, such as gene expression [29][30][31][32][33][34][35] or RNA metabolism [36]. This means that the DDR pulls players from various cellular processes out of their regular context and assigns them temporary tasks under its command.…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
“…ATM kinase, which is defective in the hereditary cancer-prone disorder ataxia-telangiectasia (A-T), is activated by DSBs and phosphorylates a variety of proteins involved in the DNA damage response, leading to cell cycle checkpoint activation, DNA repair, altered gene expression patterns, and/or apoptosis (26). Among the ATM substrates are several transcription factors, including p53 (29), BRCA-1 (30), ATF2 (31), cyclic AMPresponsive element binding protein (32), E2F1 (33), and nuclear factor-nB regulators NEMO and IKK (34). ATR, which responds to bulky lesions and single-strand DNA generated by stalled replication forks or the DSB repair process, shares many substrates with ATM.…”
Section: ¶-(G/t)gggcgg(g/a)(g/a)(g/t)-3 ¶] Via Threementioning
confidence: 99%